Identifying and eliminating cell culture process variability. (December 2014) - Gilbert, Alan; Huang, Yao-ming; Ryll, Thomas
Critical to the biopharmaceutical industrial objectives are robust, reproducible processes which result in consistent product quality and yields. These parameters support the product safety and efficacy as well as control over the process and supply chain. To have a consistent cell culture process, process inputs must be reliable. Historically cell culture media have been a source of variability through the inclusion of complex components such as hydrolysates and sera. Industry has shifted to chemically defined basal and feed media and seen reduced variability but chemically defined media have not eliminated process variability. This review will consequently focus on media variability, the subsequent outputs of lactate and ammonia production and product quality, and the possible routes to eliminate process inconsistency.